Multifaceted analysis of nanotoxicity using primary cultured neurons. (1st September 2022) - Kamikubo, Yuji; Yamana, Tomohito; Inoue, Yuriko; Sakurai, Takashi
Abstract: Various nanomaterials have been produced with the development of nanotechnology, some of which have been reported to have adverse effects on several types of cells, organs, and the environment. It has been suggested that some small nanoparticles can cross the blood-brain barrier and accumulate in the brain, which may be a potential cause of brain diseases. Neuronal cells are vulnerable to hypoxia, hypotrophy, and mechanical and oxidative stress. Therefore, it is essential to assess the toxicity of nanoparticles to neurons accurately. In this report, we describe a primary culture protocol to evaluate the toxicity of nanoparticles on neurons, a potential high-throughput method for assessing the cytotoxicity, and a method for evaluating the effect on neuronal maturation. This report assessed the toxicity of silicon dioxide, zinc oxide, and iron nanoparticles using rat hippocampal neurons, which are used frequently in pharmacological and physiological studies. Based on the methods and protocols we reported in this report, it may be possible to evaluate nanotoxicity to various neurons by using primary cultures of other brain regions (cerebral cortex, cerebellum, thalamus, etc.), spinal cord, and peripheral nerves.